Pengaruh Model Pembelajaran RADEC untuk Meningkatkan Kemampuan Numerasi Matematis Siswa berbasis Budaya Melayu berbantuan Canva - Malika Thahara; Yumira Simamora; Israq Maharani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model based on Malay culture assisted by Canva on the mathematical numeracy abilities of eighth-grade students at SMP Negeri 25 Medan in the 2025/2026 academic year. The research method used was true experimental design with a posttest-only control group design. The research population consisted of 220 eighth-grade students, with a sample of 61 students comprising class VIII-C as the experimental group and class VIII-D as the control group. The experimental class received treatment using the RADEC model based on Malay culture with Canva media, while the control class used conventional learning. The research instrument was a mathematical numeracy ability test covering three aspects: using numbers and symbols, analyzing graphic and table forms, and interpreting decision results. Descriptive analysis results showed that the average posttest score of the experimental class was higher than the control class in every numeracy aspect. Prerequisite tests indicated that the data were normally distributed and homogeneous. Hypothesis testing using t-test yielded a t-value of 2.001 with significance less than 0.05, indicating a significant difference between the two groups. This study concludes that the RADEC learning model based on Malay culture assisted by Canva has a positive and significant effect on improving students' mathematical numeracy abilities. This model proved effective in enhancing learning outcomes across all numeracy indicators and making learning more contextual, engaging, and meaningful for students.